EFFECT OF DIHYDROXY FLAVONES ON MORPHINE TOLERANCE: Life Science-Pharmacology - KAMALAKANNAN P; VIDYALAKSHMI K; BINOY VC; BHAARATI GM; VISWANATHAN S; RAMASWAMY S (International Journal of Life Science and Pharma Research, 2012)
Flavonoids like gossypin and quercetin were earlier demonstrated to suppress the development of morphine tolerance. The present study investigated the effect of four dihydroxy flavone compounds (3,2’- dihydroxy flavone, 3,3’- dihydroxy flavone, 3,4’- dihydroxy flavone and 5,7,- dihydroxy flavone) on the development of tolerance to morphine antinociception in mice. Mice were treated with increasing doses of morphine (s.c.) for five days from 10 mg/kg/day with an increment of 5 mg/kg every alternate day. Different groups of mice were pretreated with the above dihydroxy flavones 30 minutes prior to morphine injection every day. On the sixth day, the antinociceptive effect of morphine (1 mg/kg, s.c.) was assessed in all the above treatment groups by employing acetic acid induced abdominal constriction assay and warm water tail immersion assay. Chronic treatment with morphine for five days resulted in decrement of analgesic response on the sixth day. The number of abdominal constrictions was significantly increased in morphinetolerant animals compared to naïve mice. A similar attenuation of morphine-antinociceptive effect was recorded in tail immersion assay in mice exposed to morphine treatment for five days as revealed by a reduction in tail flick latency compared to morphine naïve mice. Pre-treatment with different dihydroxy flavone compounds did not alter the response recorded in morphine tolerant mice. This observation indicated that the investigated dihydroxy flavones failed to modulate the development of tolerance to morphine antinociception in mice